Competitiveness and Brand of Tourist Destinations in Peru: A Proposal for Development 2019-2021 - Cueto Luna, María Guislena (2019)
In terms of tourism activity, competitiveness is usually reflected in the midst of a series of material and non-material elements that determine the quality and differentiation of the tourism product within a given area, whose main purpose is to meet the needs of comfort and well-being of tourists, which must represent an effort of government authorities, business associations and academics in their treatment, proposing viable and sustainable tourism business models not only economically but socially, culturally and environmentally; since all tourism development options must have an effective impact on the improvement of the quality of life of the tourist destination population. In the current globalized markets, the establishment of destination brands helps to identify and differentiate the great diversity of tourist products, form a position and have it as a strategy of generating wealth not only serve to manage the brand value but to preserve the value of the socio-cultural heritage of the targeted areas, avoiding their politicization and maintaining the attraction of travelers and investors should be a path that we must not lose sight of.